Analyzing The Impact Of Work Discipline, Work Motivation, And Job Satisfaction On The Performance Of Air Traffic Controllers At The Perum LPPNPI MATSC - Laraswati, Niken Yulian; Laba, Abd. Rakhman; Ismail, Muhammad (YUME : Journal of Management, 2023)
Work discipline, work motivation, and job happiness are just a few of the variables that may affect how well an organization uses its human resources to achieve its objectives. The purpose of this study is to investigate the potential effects of job satisfaction, motivation, and work discipline on air traffic controller performance. To examine the correlations between the variables, the study uses quantitative research techniques. One hundred respondents will have their information gathered via a questionnaire in order to establish a causal link. Work discipline did not significantly affect performance, according to the study, as evidenced by a path coefficient of 0.072 and a p-value of 0.300, both of which are higher than the 0.05 cutoff. A low coefficient of determination (f square = 0.008) thus indicates very poor work discipline and performance of structural ATC. Performance and motivation are highly correlated, as indicated by a p-value of less than 0.05 and a path coefficient of 0.380. ATC performance is affected by any change in motivation. Performance and structure-level motivation have a rather robust association (effect size = 0.299). A path coefficient of 0.499 and a p-value of 0.000 (smaller than the significance level of 0.05) show that job satisfaction has a significant impact on performance. This implies that performance is impacted by changes in satisfaction. With a f square score of 0.399, the structural degree of job satisfaction and performance is good. Kata Kunci: discipline; motivation; satisfaction; performance; atc